Overlapping Features in Kawasaki Disease-Related Arthritis and Systemic-Onset Juvenile Idiopathic Arthritis: A Nationwide Study in Japan - Hikaru Kanemasa; Etsuro Nanishi; Hidetoshi Takada; Hidetoshi Takada; Masataka Ishimura; Hisanori Nishio; Satoshi Honjo; Hiroshi Masuda; Noriko Nagai; Takahiro Nishihara; Tohru Ishii; Takenori Adachi; et al. (Frontiers Media S.A., 2021)
Background: Arthritis may occur after the diagnosis of Kawasaki disease (KD). Most cases are self-limiting; however, some patients require prolonged treatment.Method: To characterize KD-related arthritis, 14 patients who required arthritis treatment within 30 days after the diagnosis of KD were recruited from the 23rd KD survey in Japan. Twenty-six additional patients were included from our tertiary center and literature review cohorts.Results: The estimated prevalence of KD-related arthritis in Japan was 48 per 100,000 KD patients. Patients with KD-related arthritis had an older age at onset (52 vs. 28 months, P = 0.002) and higher rate of intravenous immunoglobulin (IVIG) resistance in comparison to those without arthritis (86 vs. 17%, P < 0.001). Among 40 patients, 18 had arthritis in the acute phase KD (continued fever-onset type) and 22 did in the convalescent phase (interval fever-onset type). Both showed a similar rate of complete KD or IVIG response. Interval-type patients required biologics for arthritis control less frequently (5 vs. 39%, P = 0.02) and had a higher 2-year off-treatment rate (100 vs. 43%, P = 0.009) than continued-type ones. Interval-types showed lower serum ferritin and interleukin-18 levels than continued-types. When continued-types were grouped according to whether or not they required biologics (n = 7 and n = 11, respectively), the former subgroup had higher ferritin and interleukin-18 levels (P = 0.01 and 0.02, respectively). A canonical discriminant analysis differentiated interval-type from continued-type with the combination of age, time to arthritis, and the ferritin and matrix metalloproteinase-3 levels.Conclusion: Arthritis requiring treatment is a rare complication of KD. KD-associated arthritis includes interval-type (KD-reactive) and continued-type (true systemic-onset juvenile idiopathic arthritis [JIA] requiring biologics), and overlapping arthritis, suggesting the pathophysiological continuity of autoinflammation between KD and JIA.